# If x + 1 is a fac

let p(x) = ax3 + x2 – 2x + 4a – 9 and g(x) = x + 1

Putting g(x) = 0 x + 1= 0 x = – 1

According to the factor theorem if g(x) is a factor of p(x) then p ( – 1) = 0

p( – 1) = a( – 1)3 + ( – 1)2 – 2( – 1) + 4a – 9 = 0

3a – 6 = 0 a = 2

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses RELATED QUESTIONS :

Factorize:
</p
RS Aggarwal & V Aggarwal - Mathematics

Find the vaRS Aggarwal & V Aggarwal - Mathematics

Factorize:
</p
RS Aggarwal & V Aggarwal - Mathematics

Factorize:
</p
RS Aggarwal & V Aggarwal - Mathematics

If <span lang="ENNCERT Mathematics Exemplar

Show that p – 1 iNCERT Mathematics Exemplar

Factorize:
</p
RS Aggarwal & V Aggarwal - Mathematics

Find the value ofNCERT Mathematics Exemplar

In each of the foRD Sharma - Mathematics